Consumer influence on lightweight packaging waste generation in Germany - Jannick Schmidt; Maximilian Auer; Roman Maletz; Viola Galler; Jörg Woidasky (Cleaner and Responsible Consumption, 2024)
A two-week field study was conducted in 2019 to investigate the generation of German lightweight packaging (LWP) waste. The study involved 249 selected households throughout the country, and a total of 254,032 g (25,762 items) of LWP were analyzed. Participating households completed a questionnaire providing information on e.g., household and municipality size, as well as the local collection system. The annual LWP waste generation per capita (9.5 kg) was lower than the official German statistical 2019 data (32 kg). Smaller households led to higher waste generation per person. Furthermore, the study revealed a 14% rise in per capita waste generation among participants who did not correctly identify their collection system. A further sample of 207,138 g (21,380 items), taken from the total mass, was analyzed in more detail, revealing a 22.8% (w/w) share of polyolefins and a 29.5% (w/w) share of flexible packaging. In addition, the packaging contained an average of 7.7% (w/w) residual contents and 8.8% (w/w) incorrectly disposed waste. The study results indicate that consumer behavior, as well as external factors such as household size and local collection systems, can directly influence the quantity, weight, and to some extent, the quality (share of incorrectly disposed waste) of LWP waste. These observations reveal possible approaches to achieve higher recycling rates and qualities of plastic packaging in the LWP waste management value chain.